Somewhere we are human : authentic voices on migration, survival, and new beginnings - Grande, Reyna; Guiñansaca, Sonia (HarperVia, an imprint of HarperCollinsPublishers, 2022)
"Introduction by Pulitzer Prize-winning author Viet Thanh Nguyen-- A unique collection of 44 groundbreaking essays, poems, and artwork by migrants, refugees and Dreamers--including award-winning writers, artists, and activists--that illuminate what it is like living undocumented today. In the overheated debate about immigration, we often lose sight of the humanity at the heart of this complex issue. The immigrants and refugees living precariously in the United States are mothers and fathers, children, neighbors, and friends. Individuals propelled by hope and fear, they gamble their lives on the promise of America, yet their voices are rarely heard. This anthology of essays, poetry, and art seeks to shift the immigration debate--now shaped by rancorous stereotypes and xenophobia--towards one rooted in humanity and justice. Through their storytelling and art, the contributors to this thought-provoking book remind us that they are human still. Transcending their current immigration status, they offer nuanced portraits of their existence before and after migration, the factors behind their choices, the pain of leaving their homeland and beginning anew in a strange country, and their collective hunger for a future not defined by borders. Created entirely by undocumented or formerly undocumented migrants, Somewhere We Are Human is a journey of memory and yearning from people newly arrived to America, those who have been here for decades, and those who have ultimately chosen to leave or were deported. Touching on themes of race, class, gender, nationality, sexuality, politics, and parenthood, Somewhere We Are Human reveals how joy, hope, mourning, and perseverance can take root in the toughest soil and bloom in the harshest conditions"--